A Rare Presentation of Primary Hyperparathyroidism with Concurrent Aldosterone-Producing Adrenal Carcinoma. (16th June 2015) - Molina-Ayala, Mario; Ramírez-Rentería, Claudia; Manguilar-León, Analleli; Paúl-Gaytán, Pedro; Ferreira-Hermosillo, Aldo
Abstract : Aldosterone-producing adrenocortical carcinomas are an extremely rare cause of hyperaldosteronism (<1%). Coexistence of different endocrine tumors warrants additional screening for multiple endocrine neoplasia syndromes, especially in young patients with large or malignant masses. We present the case of a 40-year-old man with a history of hypertension that presented with an incidental left adrenal tumor during an ultrasound performed for nephrolithiasis. Biochemical assessment showed a mildly elevated calcium (11.1 mg/dL), high parathyroid hormone, and a plasma aldosterone concentration/plasma renin activity ratio of 124.5 (normal < 30), compatible with primary hyperparathyroidism with a concomitant primary hyperaldosteronism. A Tc99m-MIBI scintigraphy showed an abnormally increased tracer uptake in the right superior parathyroid and abdominal computed tomography confirmed a left adrenal tumor of 20 cm. The patient underwent parathyroidectomy and adrenalectomy with final pathology reports of parathyroid hyperplasia and adrenal carcinoma with biochemical remission of both endocrinopathies. He was started on chemotherapy, but the patient developed a frontal cortex and an arm metastasis and finally died less than one year later.